2011
DOI: 10.1002/gps.2677
|View full text |Cite
|
Sign up to set email alerts
|

Influence of personality on caregiver's burden, depression and distress related to the BPSD

Abstract: Objective: We hypothesize that the personality influences the caregiver's depression, burden and distress related to BPSD. Subjects and methods: Participants were 105 consecutive patients with dementia and their family caregivers, living at home, attending a Dementia Clinic. A cross-sectional design was used with an applied a structured interview at home. Comprehensive assessments included: personality (NEO-FFI), burden (ZBI), depression (CES-D) and distress related to BPSD (NPI-distress). Statistical Path ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 46 publications
(59 reference statements)
7
51
0
5
Order By: Relevance
“…It is likely that there are other factors inherent to the carers themselves that have important contributions to depression, such as carer personality. Neuroticism, in particular, has been found to be significantly associated with depression and burden [3,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that there are other factors inherent to the carers themselves that have important contributions to depression, such as carer personality. Neuroticism, in particular, has been found to be significantly associated with depression and burden [3,23].…”
Section: Discussionmentioning
confidence: 99%
“…They are more likely to have poor physical health, and report lower quality of life [2,3]. Some authors have suggested that older carers are at the highest risk of these adverse effects [4,5].…”
Section: Introductionmentioning
confidence: 97%
“…It has been suggested that people expressing neuroticism need better coping methods and relaxation strategies, in order to decrease their psychological distress [11]. In contrast, a high level of extroversion in caregivers of patients with dementia appears to be protective, with data showing it is associated with decreased CB and depression, which may contribute to an improved QoL [16]. One recent study investigating familial caregivers of community-dwelling older adults with multiple functional impairments demonstrated that whilst extroversion was positively associated with better physical and mental health, neuroticism showed a negative relationship [17].…”
Section: Introductionmentioning
confidence: 99%
“…18 It has been reported that symptoms such as delusions, agitation/aggression, anxiety, irritability/lability, and dysphoria/depression are strongly associated with higher caregiver burden. 19 These symptoms may arouse negative feelings, such as entrapment, shame, or guilt, which may lead to higher levels of depression and physical symptoms.…”
Section: Disease Awareness and Dementia Symptomsmentioning
confidence: 99%